Comparative assessment of the VH-VL and VL-VH orientations of single-chain variable fragments of scorpion toxin-neutralizing antibodies. (June 2020) - Riaño-Umbarila, Lidia; Rojas-Trejo, Vianey Margarita; Romero-Moreno, José Alberto; Costas, Miguel; Utrera-Espíndola, Irving; Olamendi-Portugal, Timoteo; Possani, Lourival D.; Becerril, Baltazar
Highlights: The orientation of the VL-VH domains of a scFv can change some properties. The new VL-VH orientation of two scFvs modified expression levels. There were no differences in terms of functional activity and affinity. Calorimetric studies confirmed that the two orientations had the same stability. Abstract: The present study evaluated the effect of the change in the orientation of the VH-VL variable domains to VL-VH on the physicochemical and functional properties of two scorpion toxin-neutralizing scFvs. The results showed that the level of expression of proteins obtained from the periplasm of E. coli is the factor mainly affected, either with an increase or decrease in the amount of protein recovered. Likewise, the functional recognition activity in the presence of a denaturing agent showed slight variations in the two orientations. In contrast, recognition and biological activity (neutralizing capacity) are maintained. At the interaction level, the change marginally modified the kinetic association and dissociation constants without significantly modifying the value of the affinity constants. Similarly, it was observed that the thermodynamic stability of the proteins did not show significant variations either. These results contrast with some reports of the effect of changing the orientation of domains, suggesting that it is not possible to predict which orientation of the variable domains of an scFv is more favorable or if they are equivalent, as in the case of scFvs previously matured by directed evolution techniques.